Adverse Effects of Systemic Immunosuppression in Keratolimbal Allograft - M. Krakauer; J. D. Welder; H. K. Pandya; N. Nassiri; A. R. Djalilian (Journal of Ophthalmology)
Purpose. Keratolimbal allograft (KLAL) is a treatment for limbal stem cell deficiency. One disadvantage is systemic immunosuppression to avoid rejection. Our purpose was to examine the adverse effects of systemic immunosuppression in KLAL. Methods. A retrospective case review of 16 patients with KLAL who received systemic immunosuppression consisting of a corticosteroid, an antimetabolite, and/or a calcineurin inhibitor was performed. Patients were monitored for signs, symptoms, or laboratory evidence of toxicity. Results. Twelve of 16 patients (75%) experienced an adverse effect. The average age of those with adverse effects was 50.0 years (SD 17.8) and those without was 23.6 years (SD: 14.3), which was statistically significant (unpaired t-test P=0.022). Ten of 11 patients (91%) had resolution during mean followup of 16.4 months. No serious adverse effects occurred. The most common included anemia, hyperglycemia, elevated creatinine, and elevated liver function tests. Prednisone and tacrolimus were responsible for the most adverse effects. More patients with comorbidities experienced adverse effects (83%) than those without comorbidities (25%). Conclusions. KLAL requires prolonged systemic immunosuppression. Our data demonstrated that systemic immunosuppression did not result in serious adverse effects in our population and is relatively safe with monitoring for toxicity. In addition, we demonstrated that adverse effects occurred more frequently in older patients and those with comorbidities.